Effects of changing physiologic conditions on the in vivo quantification of hemodynamic variables in cerebral aneurysms treated with flow diverting devices. (30th August 2013) - Mut, Fernando; Ruijters, Danny; Babic, Drazenko; Bleise, Carlos; Lylyk, Pedro; Cebral, Juan R.
SUMMARY Quantifying the hemodynamic environment within aneurysms and its change after deployment of flow diverting devices is important to assess the device efficacy and understand their long‐term effects. The purpose of this study was to estimate deviations in the quantification of the relative change of hemodynamic variables during flow diversion treatment of cerebral aneurysms due to changing physiologic flow conditions. Computational fluid dynamics calculations were carried out on three patient‐specific geometries. Three flow diverters were virtually implanted in each geometry and simulations were performed under five pulsatile flow conditions. Hemodynamic variables including aneurysm inflow rate, mean velocity, shear rate, and wall shear stress were quantified before and after stenting. Deviations in the relative change of these variables due to varying flow conditions were calculated. The results indicate that a change in the mean flow of the parent artery of approximately 30–50% can induce large deviations in the relative change of hemodynamic variables in the range of 30–80%. Thus, quantification of hemodynamic changes during flow diversion must be carried out carefully. Variations in the inflow conditions during the procedure may induce large deviations in the quantification of these changes. Copyright © 2013 John Wiley & Sons, Ltd.